Process Evaluation of a Pilot Food Insecurity Resource Navigation Program Integrated Within Pediatric Primary Care: Utilizing RE-AIM to Inform Program Scale-up - Stuenkel, Mackenzie; Koob, Caitlin; Richardson, Emily; Smolens, Nicole; Eicken, Meredith; Amati, J Blakely; Sease, Kerry (Journal of public health management and practice, 2024)
The purpose of this study was to examine the implementation and effectiveness of a novel pediatric food navigation program through a structured, comprehensive evaluation using the RE-AIM framework. Data were collected from October 2021 through August 2022 for 166 pediatric patients and their families who were screened as food insecure or high-risk for food insecurity and were referred to this pilot food resource navigation program (FRNP). A total of 88 patients' guardians consented to participate in this FRNP, receiving initial service connection. Participants were contacted via telephone by trained navigators within this health system to assess food security status across three time points (baseline, follow-up 1 [1- <3 months], and follow-up 2 [3-6 months]) and facilitate connection to appropriate community-based resources related to food assistance. In this sample, we had an overrepresentation of Hispanic patients and an underrepresentation of Non-Hispanic Black and White patients relative to the available clinic population. Patients participating in the navigation program showed incremental shifts toward food security from baseline to two follow-up points. Integration within primary care was supported by physician champions across participating clinics and alignment with systemwide, updated universal screening guidelines to support projected increases in families requiring connecting to assistance programs. Through this evaluation, a comprehensive list of community-based food resource programs related to food assistance was integrated into electronic documentation for navigators to alleviate navigator burden and sustain the effect of this FRNP's implementation. These findings may be used to inform expansion of current programming efforts within this FRNP and to clarify process evaluations of broader health system-based programming. Further research, building on the findings of this pilot study, is needed to examine the longitudinal, causal effect of FRNPs in pediatric food security and long-term health outcomes for replication across health systems nationwide.